Direct observation of the conical intersection in cis-trans photoisomerization of rhodopsin - Polli, D; Manzoni, C; Brida, D; Cerullo, G; Altoe, P; Tomasello, G; Orlandi, G; Garavelli, M; Weingart, O; Kukura, P; Spillane, K; Mathies, R (Optical Society of America, 2009)
High-time-resolution broadband pump-probe spectroscopy of rhodopsin reveals the loss of reactant and appearance of photoproduct features within ≈100fs, which are signatures of a wavepacket moving through a conical intersection. Experiments are supported by molecular dynamics simulations. © Optical Society of America.